A = (2x + 3) (5x - 2) + 2x²
A = 2x * 5x + 2x * (- 2) + 3 * 5x + 3 * (- 2) + 2x²
A = 10x² - 4x + 15x - 6 + 2x²
A = 12x² + 11x - 6
B = 4x² + 5 + (2x - 4) (3x + 6)
B = 4x² + 5 + 2x * 3x + 2x * 6 - 4 * 3x - 4 * 6
B = 4x² + 5 + 6x² + 12x - 12x - 24
B = 10x² - 19
C = 5x + 3 + (2x - 4) (2x + 4)
C = 5x + 3 + (2x)² - 4²
C = 5x + 3 + 4x² - 16
C = 4x² + 5x - 13
D = (3 + 4x) (- 2x - 5) - 6x² + 2
D = 3 * (- 2x) + 3 * (- 5) + 4x * (- 2x) + 4x * (- 5) - 6x² + 2
D = - 6x - 15 - 8x² - 20x - 6x² + 2
D = - 14x² - 26x - 13